2001
DOI: 10.33584/jnzg.2001.63.2403
|View full text |Cite
|
Sign up to set email alerts
|

Farm systems - Impact of stocking rate on dairy farm efficiency

Abstract: Two years of results from a 10 farmlet, farm systems trial (ending May 2001) are presented. The trial was designed to determine the efficiency and profitability of milksolids production when annual drymatter intake/cow and subsequent milksolids production/cow is increased within a whole farm system. Operating within the trial were five levels of feed intake and two farm management systems. The data presented show that with increasing kg liveweight/tonne of drymatter/ha, there was an increase in efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 1 publication
4
21
1
Order By: Relevance
“…The results of this analysis indicate that as SR increases, total DMI per 100 kg of BW is reduced as a similar amount of energy is partitioned to body tissue, resulting in reduced energy availability for milk production and reduced MS production per 100 kg of BW. Similarly, Macdonald et al (2001) previously observed that as individual animal DMI is reduced at higher SR and milk production per cow is reduced, an increasing proportion of the feed eaten is used for maintenance and pregnancy, thus reducing gross feed efficiency of milk production. The results of this study also indicate that the net feed efficiency (UFL of NEI; MS production per UFL available for production after maintenance) increases at higher SR and reflects the reduced utilization of energy for BW gain of animals at higher SR reported previously by McCarthy et al (2012).…”
Section: Effect Of Sr CD and S On Dha Milk Production Bw Bcs Anmentioning
confidence: 70%
“…The results of this analysis indicate that as SR increases, total DMI per 100 kg of BW is reduced as a similar amount of energy is partitioned to body tissue, resulting in reduced energy availability for milk production and reduced MS production per 100 kg of BW. Similarly, Macdonald et al (2001) previously observed that as individual animal DMI is reduced at higher SR and milk production per cow is reduced, an increasing proportion of the feed eaten is used for maintenance and pregnancy, thus reducing gross feed efficiency of milk production. The results of this study also indicate that the net feed efficiency (UFL of NEI; MS production per UFL available for production after maintenance) increases at higher SR and reflects the reduced utilization of energy for BW gain of animals at higher SR reported previously by McCarthy et al (2012).…”
Section: Effect Of Sr CD and S On Dha Milk Production Bw Bcs Anmentioning
confidence: 70%
“…The decrease in mean post‐grazing pasture mass with increased stocking rate (from 2·5 to 3·8 cows ha −1 ) for CMS treatments is in line with the earlier findings of Macdonald et al . () who evaluated the impact of stocking rate in pasture‐based systems on dairy‐farm efficiency. However, post‐grazing pasture mass for AMS and HSR was similar, despite the intermediate AMS stocking rate (3·1 cows ha −1 ) between CMS treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Even though supplement was used to fill feed deficits, our findings and those of Macdonald et al . () suggest that either the level, or quality of, supplement offered under current grazing management guidelines was insufficient to maintain post‐grazing residuals or that the amount of pasture actually on offer was less than that estimated. This could be due to an underestimation of the energetic requirements of dairy cattle, an overestimation of supplement utilization, or that cows prefer pasture over supplement, with resulting supplement wastage and poor utilization.…”
Section: Discussionmentioning
confidence: 99%
“…A range of allowances were allocated to each strain at which they were expected to be farmed successfully, ranging from moderate feed restriction up to generous feeding levels (4.5 to 7.0 t of DM/cow per yr; Table 2). Evidence from a previous experiment (Macdonald et al, 2001) indicated that the economically optimum CSR was between 85 and 90 kg of BW/t of DM. Thus, the CSR for this experiment were set to range below and above this optimum point.…”
Section: Feed Allowancesmentioning
confidence: 92%